2018
DOI: 10.1002/aoc.4226
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles supported on ionic‐tagged magnetic hydroxyapatite as a highly efficient and reusable nanocatalyst for hydrogenation of nitroarenes in water

Abstract: A novel chemically modified magnetic hydroxyapatite (MHAp) was prepared and used as support and stabilizer for the synthesis of silver nanoparticles. First, 1,4-diazabicyclo[2.2.2]octane (DABCO) was successfully grafted onto the surface of MHAp, and then silver nanoparticles were homogeneously loaded on mesoporous MHAp-DABCO (ionic-tagged MHAp) nanocomposite by in situ chemical reduction of silver nitrate using sodium borohydride. The structure and properties of the resulting MHAp-DABCO-Ag nanocomposite were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…The magnetic property of FeS x ‐Fe 2 O 3 @CN‐ 8 was measured by the Quantum Design SQUID MPMS‐XL7 magnetometer. As shown in Figure 6a, the magnetic hysteresis loop for developed FeS x ‐Fe 2 O 3 @CN‐ 8 catalyst exhibits a saturated magnetization of 10.4 emu g −1 at 5,500 Oe at 293 K. [ 63,64 ] As shown in Figure 6a inset, the FeS x ‐Fe 2 O 3 @CN‐ 8 catalyst could also be easily separated by an external magnet and reused after thoroughly washed with ethanol, further supporting above the magnetic analysis. [ 65 ] The recyclability test (Figure 6b) suggested that FeS x ‐Fe 2 O 3 @CN‐ 8 catalyst could be consecutive reused for five times without obvious loss of activity.…”
Section: Resultsmentioning
confidence: 56%
“…The magnetic property of FeS x ‐Fe 2 O 3 @CN‐ 8 was measured by the Quantum Design SQUID MPMS‐XL7 magnetometer. As shown in Figure 6a, the magnetic hysteresis loop for developed FeS x ‐Fe 2 O 3 @CN‐ 8 catalyst exhibits a saturated magnetization of 10.4 emu g −1 at 5,500 Oe at 293 K. [ 63,64 ] As shown in Figure 6a inset, the FeS x ‐Fe 2 O 3 @CN‐ 8 catalyst could also be easily separated by an external magnet and reused after thoroughly washed with ethanol, further supporting above the magnetic analysis. [ 65 ] The recyclability test (Figure 6b) suggested that FeS x ‐Fe 2 O 3 @CN‐ 8 catalyst could be consecutive reused for five times without obvious loss of activity.…”
Section: Resultsmentioning
confidence: 56%
“…We are interested in the study on Ag nanocatalysis because it is a promise and undeveloped area. As we and other groups reported, [23][24][25][26][27][28] the high activity and selectivity for hydrogenation of the aromatic nitro compounds on the silver-loaded heterogeneous catalyst have been achieved, such as chemoselective hydrogenation of chloronitrobenzenes on Ag/Y 2 O 3 nanobelt catalyst 26 and Ag/C 60 catalyst 27 to corresponding chloroanilines without any hydrodehalogenation.…”
Section: Introductionmentioning
confidence: 60%
“…Silver-loaded catalysts have attracted scientists' attention and several works have been reported. [23][24][25][26][27] But, as comparison with gold catalysts, the study on catalytic hydrogenation of silver nanoparticles is relatively rare despite its' excellent catalytic performance. We are interested in the study on Ag nanocatalysis because it is a promise and undeveloped area.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few examples of heterogeneous catalysts for selective hydrogenation of only one nitro group when two are present in the same molecule, and a number of them use NaBH 4 as a reducing agent. [73][74][75][76] There are only a few examples where hydrogen is used instead, and all of them rely on rare and expensive metals like ruthenium, 77 platinum-palladium alloy, 78 or gold. 79,80 Recently, our group developed a silver-based system also using rice husk ashes as a support, with the same selectivity.…”
Section: View Article Onlinementioning
confidence: 99%